Speech perception in complex acoustic environments - Viveros Muñoz, Rhoddy A. (Logos Verlag Berlin, 2019)
Listeners with hearing impairments have difficulties understanding speech in the presence of background noise. Although prosthetic devices such as hearing aids and cochlear implants may improve the hearing capability, listeners with hearing impairments still complain about their speech perception in the presence of noise. The basic tonal audiometry only gives a cursory idea of the degree of difficulty in spoken communication caused by hearing loss because it does not assess the ability to understand speech. Therefore, the use of speech-in-noise tests to measure hearing loss in complex scenes is an integral part of a patient's audiological study. Most research has concentrated on studying only stationary sound sources, but in natural acoustic scenes, conversations may become very difficult to understand in the presence of moving sound sources such as a moving talker or a passing vehicle. Therefore, this thesis deals with quantifying speech perception in the presence of moving maskers through virtual sound sources presented binaurally via headphones. Significant differences in several conditions were found, revealing that the auditory system assesses differently the moving maskers than the stationary maskers. Therefore, the inclusion of moving conditions in clinical listening tests is recommended, in order to assess speech-in-noise perception in a more realistic environment.